INSERTING LOCAL WISDOM MATERIALS TO ENHANCE STUDENTS CONFIDENCE IN SPEAKING SKILL - Prayudha.S, Joko (Journal of Language, Literature and Teaching, 2023)
Speaking skills are one of the most productive language skills. The ability to speak makes students able to produce utterances so that students can speak using a language. However, in reality there are still many students who are not optimal when asked to speak English well. There are still many students who lack confidence when practicing their speaking skills in front of the class, such as speeches, conversations, small talks, even questions and answers. Therefore, this research aims to increase students' self-confidence in speaking skills through integrating material using local wisdom. This type of research is qualitative by explaining the application of learning through local wisdom in English classes. Data was obtained through a literature study by collecting several sources related to the use of local wisdom material, and interviews with two English teachers. Data was analyzed through data reduction, data display, and conclusion. The research results show that the use of local wisdom can be used as a way to make students feel more confident when speaking English, this is because the material used is familiar and they often encounter it so it is easy for students to explain a description of a place, tourist attraction or object. other. Apart from that, the use of local wisdom material is able to build students' cultural awareness of local culture.